Signaling Peptides and Receptors Coordinating Plant Root Development. (April 2018) - Oh, Eunkyoo; Seo, Pil Joon; Kim, Jungmook
Abstract : Small peptides mediate cell–cell communication to coordinate a variety of plant developmental processes. Signaling peptides specifically bind to the extracellular domains of receptors that belong to the receptor-like kinase family, and the peptide–receptor interaction activates a range of biochemical and physiological processes. The plant root is crucial for the anchorage of plants in soil as well as for the uptake of water and nutrients. Over recent years great progress has been made in the identification of receptors, structural analysis of peptide–receptor pairs, and characterization of their signaling pathways during plant root development. We review here recent advances in the elucidation of the functions and molecular mechanisms of signaling peptides, the peptide–receptor pairs that activate signal initiation, and their signaling pathways during root development. Highlights: Small peptides are emerging as key signaling molecules in coordinating various aspects of plant root development. Small signaling peptides are usually recognized by the extracellular domains of transmembrane proteins belonging to the receptor-like kinase family, and SERK family receptor-like kinases function as coreceptors for the peptide–receptor-like kinase pair activation via peptide-induced heterodimerization and transphosphorylation. Small signaling peptides and their receptors modulate plant root development in response to changing levels of nitrogen in the soil as well as to adverse environmental conditions. Small peptides can act as both long-distance signals and as local signals for root responses, acting via receptors located in different plant tissues.